(untitled) (Heritage, 2022)
Fearing that the new Young Turk government might demand the return of Bosnia and Herzegovina, Austro-Hungary took the position that the time had come to implement its earlier projects on the annexation of this territory.On October 6, 1908, Emperor Francis Joseph officially issued a proclamation “expanding the sovereignty“ of the Habsburg house over that province. The day before, Bulgaria proclaimed its national independence. The proclamation of Bulgarian independence and annexation of Bosnia and Herzegovina significantly upset the balance in the Balkans in favour of the Central Powers. Russia demanded that the issue of annexation be resolved at an international conference.Thus, Russia wanted to extract appropriate compensations for Serbia and Montenegro. Russia was immediatelly joined by its allies France and England, but also by Italy, which did not like the strengthening of Austro-Hungary in the Balkans. The governments of the Kingdom of Serbia and the Principality of Montenegro sent emissaries to all important European capitals. Serbia and Montenegro sought to conclude a military convention with Turkey. Negotiations with the Ottoman Empire with the mentioned goal were first initiated by Serbia in mid-October, 1908. Concrete negotiations on the conclusion of the Serbian-Turkish military convention were held from12/25 October to 28 November / 11 December, 1908, in Constantinople, where the Government of the Kingdom of Serbia sent its special envoy Stojan Novaković, and the Government of the Principality of Montenegro sent Serdar Janko Vukotić.Serbia and Montenegro were ready to pay money in compensation to Turkey for the territory of Sandzak and conclude an alliance with Turkey on mutual defense. The conclusion of the Serbian-Turkish military convention was supposed to be the beginning of a general Balkan alliance, which would later be joined by Greece and Bulgaria. The first draft of the military convention was made by Turkey. The Serbian Government considered the proposed Turkish draft of the military convention and made a decision to adopt it with certain amendments. When the text of the convention was agreed upon after a series of meetings, the Grand Vizier announced on 23 November / 6 December, 1908, that he could not sign the convention, since due to the opening of a new assembly, the government was considered transitional and that the signing of the convention must be postponed two or three weeks, but there may be an entene cordiale (cordial agreement) between Serbia and Turkey-a form of political agreement that existed between England and France. Novaković accepted that and suggested that they immediately sign a declaration on this general agreement-entene cordiale, which would serve instead of convention. Although the text of the declaration was determined at the next meeting, it was not signed. Finally, on 28 November/11 December, 1908, the Grand Vizier informed the Serbian delegation in Constantinople about the decision of the Turkish Council of Ministers not to sign the declaration but to keep the note. At the same time, Turkish hypocritical politicians were preparing for negotiations with Austro-Hungary.The Austro-Hungarian ambassador to Constantinople, Margrave Palavićini, met with Grand Vizier Ćamil Pasha on 30 November/13 December, 1908. The negotiations were transferred from Constantinople to Vienna and entrusted to the new Turkish ambassador, where a Protocol on the Agreement was signed on 26 February, 1909, which dealt a fatal blow to the Serbian-Montenegrin hopes.